Pengaruh Iradiasi Sinar Gamma TerhadapInduksi Kalus dan Seleksi Tingkat Toleransi Padi (Oryza sativa L.) terhadap Cekaman Salinitas secara In-Vitro - Lisdyayanti, Novita Dwi; Anwar, Syaiful; Darmawati, Adriani (Berkala Bioteknologi, 2022)
The use of saline for rice cultivation needs to be support bytolerant rice varieties in saline land. The rice variety can be obtained through plant breeding programs, one of which is by physical mutation methods using gamma rays.. Physical mutation is random mutation, so we need to do selection after that treatment. Selection to get rice mutants that are tolerant of salinity stress can be done by planting on culture media that have been modified witt addition of NaCl.The perpose of this research is to examine the effect of gamma rays irradiation doses on rice callus induction and its tolerance level in saline media. This research used 2 designs, a monofactor complete randomize design at callus induction stage with a faktor in the form of gamma rays irradiation doses (0, 100, and 200 Gy) and factorial complete randomize designat the regeneration stage with a factor in form of gamma rays irradiation doses (0, 100 and 200 Gy) and the second factor is NaCl concentration (0 and 50 mM). The steps of this research were irradiation of Ciherang variety rice seed, making media for tissue culture, sterilization of rice seed explants, initiation of explants in callus induction media, subculture to regenerated media that had been modified with the addition of NaCl according to treatment, and then observation. The results showed that gamma rays irradiation could inhibit the growth of callus diameter and reduce the grofth of callus from explants of ciherang variety. All callus subcultured into regeneration media are unable to formbuds and turn black or die.